Seizures in Idiopathic Pulmonary Arterial Hypertension - Rissardo, Jamir Pitton; Caprara, Ana Letícia Fornari (International Journal of Epilepsy, 2018)
Pulmonary arterial hypertension (PAH) is a progressive pulmonary vasculopathy. A 29-year-old female patient presenting with dyspnea and syncope within 6 hours of onset was admitted to our hospital. The patient stated that she looked for a neurologist months ago because she experienced abrupt shaking limbs occurring during physical activity. She was diagnosed with focal seizure, and carbamazepine (CBZ) was started. On admission, she reported that the dyspnea had started in the last week and recurrent episodes of syncope in the last few hours. A right heart catheterization was diagnostic of PAH. She was started on spironolactone, furosemide, sildenafil, warfarin, and supplemental oxygen. On 10th admission day, the patient was seizure free and the dose of CBZ was tapered. In the follow-up, the patient remained seizure free. An investigation to search for a chronic lung disease or hypoxemia, systemic disorder, hematological disorder, and metabolic disorder was negative.
Keywords: seizure; syncope; pulmonary hypertension